Space- and time-resolved investigation on diffusion kinetics of human skin following macromolecule delivery by microneedle arrays - Wei, J.; Haridass, I.; Crichton, M.; Mohammed, Y.; Meliga, S.; Sanchez, W.; Grice, J.; Benson, Heather; Roberts, M.; Kendall, M. (Nature Publishing Group, 2018)
Microscale medical devices are being developed for targeted skin delivery of vaccines and the extraction of biomarkers, with the potential to revolutionise healthcare in both developing and developed countries. The effective clinical development of these devices is dependent on understanding the macro-molecular diffusion properties of skin. We hypothesised that diffusion varied according to specific skin layers. Using three different molecular weights of rhodamine dextran (RD) (MW of 70, 500 and 2000 kDa) relevant to the vaccine and therapeutic scales, we deposited molecules to a range of depths (0–300 µm) in ex vivo human skin using the Nanopatch device. We observed significant dissipation of RD as diffusion with 70 and 500 kDa within the 30 min timeframe, which varied with MW and skin layer. Using multiphoton microscopy, image analysis and a Fick’s law analysis with 2D cartesian and axisymmetric cylindrical coordinates, we reported experimental trends of epidermal and dermal diffusivity values ranging from 1–8 µm2 s-1 to 1–20 µm2 s-1 respectively, with a significant decrease in the dermal-epidermal junction of 0.7–3 µm2 s-1. In breaching the stratum corneum (SC) and dermal-epidermal junction barriers, we have demonstrated practical application, delivery and targeting of macromolecules to both epidermal and dermal antigen presenting cells, providing a sound knowledge base for future development of skin-targeting clinical technologies in humans.